A GESTÃO AUTÔNOMA DA MEDICAÇÃO COMO DISPOSITIVO DE FORMAÇÃO E ATENÇÃO PSICOSSOCIAL (Fiep Bulletin - online, 2024)
Introduction: Autonomous Medication Management is a strategy through which one learns to take care of the use of medications, considering their effects on all aspects of life. It starts from the recognition that each user has a unique experience with psychotropic drugs and that it is important to increase their negotiating power with the professionals who deal with their treatment. Objective: To introduce students from undergraduate courses and Multiprofessional Residency in Health to working with groups in Primary Health Care.  Methods: This is an experience report of an extension project developed with a group of psychotropic users enrolled in a Health Unit in a city in the interior of SP, held in weekly meeting spaces, mediated by the assumptions of the GAM Guides. Results: For users, the creation of a care space stands out, with easy access and the possibility of longitudinal monitoring by an interprofessional team. For the team, the highlight is expanding the list of mental health offerings beyond prescription and prescription renewal. For students, it reveals the development of attitudinal, communicational and relational skills that are favored and provoked by exposure and contact with the idiosyncrasies related to working with groups.  Conclusion: The proposal has favored reflection on the interaction of the use of psychopharmaceuticals in the individual and collective health-disease process, in addition to contributing to the recognition of knowledge from experience, integrating experiences and academic knowledge, with new approaches and therapeutic proposals combined with the use of medication.
Keywords: Autonomous Medication Management; Primary Health Care; Health Unic System; Psychotropics